Pre-breeding in common bean: prospects and utilization of local germplasm in the UDESC improvement program (Revista de Ciências Agroveterinárias, 2010)
Aiming to identify and to select landrace beans with desirable agronomic characteristics for use in breeding to the development of improved cultivars, 110 accesses from the Banco Ativo de Germoplasma of Instituto de Melhoramento e Genética Molecular - IMEGEM/UDESC were characterized and representative of genic pool from Santa Catarina State. The experiment was conducted at field in augmented block design, with four commercial genotypes as witnesses. The genotypes had been agronomic and morphologically characterized. The data were submitted to variance analysis and the genotypes compared with the witnesses by means contrasts. Great variability was observed in the germplasm studied. The results showed promising genotypes (BAF14, BAF07, BAF09 and BAF25) obtaining mean productivity, cycle, height and insertion of pod. These landrace genotypes could be incorporated into the breeding block of beans improvement program of IMEGEM/UDESC with perspectives of advances in the bean improvement.
Keywords: Phaseolus vulgaris L.; Phenotypic characterization.